Bibliometric analysis of the inflammation in diabetic cardiomyopathy - Zhu, Ning; Huang, Bingwu; Zhu, Liuyan (Frontiers in Cardiovascular Medicine, 2022)
Background: Maladaptive inflammation is implicated in the development of diabetic cardiomyopathy (DCM). This study aimed to visually analyze the global scientific output over the past two decades regarding research of inflammation associated with DCM. Methods: All relevant articles and reviews were retrieved in the Web of Science (WOS) Core Collection (limited to SCIE) using “inflammation” and “diabetic cardiomyopathy” as search terms. Articles and reviews published from January 1, 2001–February 28, 2021 were collected. Visualization analysis and statistical analysis were conducted by Microsoft 365 Excel and VOSviewer 1.6.18. Results: Totally 578 documents were finally selected for further analysis. The publications regarding inflammation and DCM increased gradually during the approximately 20 years. The most prolific country was China, with 296 documents and the most citations (9366). The most influential author groups were Lu Cai and Yihui Tan who were from the United States. The bibliometric analysis of cooccurrence keywords showed that inflammation in DCM is composed of numerous molecules (NF-Kappa B, NLRP3 inflammasome, Nrf-2, TNF-α, protein kinase C, PPARα, TLR4, p38 mitogen-activated protein kinase, TGF-β, Sirt1，and AKT), a variety of cardiac cell types (stem cell, fibroblast, cardiomyocyte, etc.), physiological processes (apoptosis, oxidative stress, autophagy, endoplasmic reticulum stress, hypertrophy, mitochondrion dysfunction and proliferation), and drugs (sulforaphane, metformin, empagliflozin and rosuvastatin). Conclusion: Our bibliometric analysis presents the characteristic and trend of inflammation in DCM and shows that research of inflammation in DCM will continue to be a hotspot.